Humanized NSG mice ‒ a modern approach to modelling systemic lupus erythematosus in preclinical research - Mochahari, Jyotirupa; Gibo, Rikngam; Syiem, Phiwansiewdor; Chetia, Purbajit (European Journal of Clinical and Experimental Medicine, 2026)
Introduction and aim. Systemic lupus erythematosus (SLE) is a complex autoimmune illness characterized by widespread immune dysregulation and involvement of several organ systems. Conventional mouse models, although crucial for understanding basic immunopathogenic pathways, inadequately mimic human-specific immunological responses, hence constraining translational relevance. This review offers a comprehensive understanding of humanized NSG mice in systemic lupus erythematosus research, outlining techniques for engraftment, model-specific immune reconstitution characteristics, and their respective applications in simulating acute and chronic disease phenotypes. Material and methods. A comprehensive analysis of studies published between 2017 to 2025 was conducted in PubMed, Scopus, Web of Science and Google Scholar database. After removing the duplicates, a total of 87 articles were employed to finalize this study. Analysis of literature. Humanized NSG mice successfully recapitulate major immunopathological features of systemic lupus erythematosus. Among numerous approaches, CD 34+ hemopoietic stem cell models best mimic chronic phenotype, while PBMC and pristane-based systems mimic acute and environmentally triggered forms. Recent advances include cytokine knock-in and HLA transgenic derivatives improving immune reconstitution and translational dependability. Conclusion. This review provides the first integrative synthesis of humanized NSG mouse models applied to systemic lupus erythematosus, highlighting their translational potential and methodological advancements from 2017–2025. Collectively, these innovations establish humanized NSG mice as essential preclinical tools bridging experimental immunology with precision medicine in lupus research and therapy development.